Filtration flow rate at low convection volume in continuous hemodiafiltration using cytokine adsorbing hemofilter does not affect cytokine clearance in an experimental model - Mototsugu Kudo; Shinya Chihara; Hiroomi Tatsumi; Yoshiki Masuda (Renal Replacement Therapy)
Abstract Background In recent years, continuous kidney replacement therapy (CKRT) with a cytokine adsorbing hemofilter (CAH) has been used in clinical practice to treat acute kidney injury associated with hypercytokinemia. Two types of CAH are available, including polymethyl methacrylate (PMMA) and polyethylenimine-coated polyacrylonitrile (AN69ST), each having distinct adsorption mechanisms. PMMA adsorbs substances with hydrophobic bases through hydrophobic interactions, resulting in occlusion of the membrane pores. AN69ST adsorbs positively charged substances through electrostatic bonds because its bulk layer is negatively charged. In both CAH, the adsorption efficiency of cytokines with large molecular weights is likely affected by filtration rather than by diffusion transfer. These adsorbing-type membranes have limitations in terms of filtration flow rate because of their low water permeability. The relationship between the adsorption effect and the filtration flow rate in CAH-CKRT has not been fully investigated. Purpose The effect of low-convection volume settings below 600 mL/h on cytokine adsorption characteristics was experimentally investigated in CKRT. Materials and methods Test solutions, including albumin (4.5%), creatinine (10 mg/dL), interleukin (IL)-6 (1000 pg/mL), and IL-8 (1000 pg/mL), were prepared. The test solution was circulated through the experimental circuit of continuous hemodiafiltration (CHDF) with a total convection volume ranging from 0 to 600 mL/h. The test solution was circulated through the experimental circuit of hemodiafiltration (CHDF) with various dialysate flow rates (QD; 0, 200, 400, and 600 ml/h) and filtration flow rates (QF; 0, 200, 400, and 600 ml/h). Samples immediately before and after CAH from the sampling port of the circuit were collected seven times at 1-min intervals. Clearances of creatinine, IL-6, and IL-8 were calculated for each setting of the proportions of QD and QF during CKRT using PMMA and AN69ST. Results Creatinine clearance increased with increasing QD and QF, regardless of the membrane type. There were no significant differences in the adsorption clearance of IL-6 and IL-8 among the different settings, regardless of the membrane type. Conclusion The results of this study indicate that the cytokine clearance at a low convection volume in CAH-CKRT was not affected by the filtration flow rate.